Guest Editorial: A purchasing and supply management view of supply resilience for better crisis response. Issue 5 (December 2022) - Kähkönen, Anni-Kaisa; Patrucco, Andrea S.
Abstract: Purchasing and supply management (PSM) has been under great pressure since the COVID-19 pandemic first shook the world. Companies and public organizations faced new kinds of supply disruptions, and at a scale never seen before. New response abilities were required from PSM to address these challenges and disruptions. This Editorial introduces four articles in the Special Issue on "PSM learning from the pandemic: transforming for better crisis management." These empirical contributions show how companies could build resilience to survive and be competitive during the COVID-19 pandemic. This Editorial discusses how supply resilience should be conceptualized in post-pandemic supply chains adopting a PSM perspective. We suggest that supply resilience practices should be developed and planned according to whether they strengthen existing supply chain relationships (bridging) or establish new ones (buffering) and whether they are short-term (temporary) or long-term (permanent) orientated. Furthermore, three supply resilience capabilities, absorbing, responding and capitalizing, should be prioritized in supply chains for responding to and recovering from global crises and disruptions. Supply resilience is key to crisis response and recovery, and PSM has an essential role in building and sustaining that resilience. Highlights: Conceptualizes supply resilience in post-pandemic supply chains adopting a PSM perspective. Shows why PSM has a key role in building and sustaining resilience. Supply resilience capabilities should be prioritized for responding to and recovering from global disruptions. Editorial introduces four articles in the Special Issue.